UPAYA SATUAN SAMAPTA DALAM PENCEGAHAN TINDAK PIDANA PENCURIAN KENDARAAN BERMOTOR DI WILAYAH HUKUM POLRES DEMAK MELALUI KEGIATAN PATROLI - JIHAN ANDREAN (Indonesian Journal of Police Studies, 2022)
ABSTRACT THE EFFORT OF THE SAMAPTA UNIT THROUGH PATROL ACTIVITIES IN PREVENTING THE CRIME OF MOTOR VEHICLE THEFT IN THE JURISDICTION OF THE POLRES OF DEMAK Jihan Andrean, No. Ak 18.044, jihanandrean1295@gmail.com The writing of this final project is motivated by the existence of information that shows that in the jurisdiction of the Demak Police, there is a fairly high number of motor vehicle thefts. motorized vehicles in the jurisdiction of the Demak Police. In this study, concepts and theories that are related to this research are used, including the concept of effort, the concept of patrolling, the concept of the Samapta Unit, the concept of motor vehicle theft, the theory of management elements, the theory of management functions, and the theory of SWOT analysis. The approach used in this research is a qualitative research approach with field research methods. Sources of data obtained in this study consisted of primary data sources in the form of interviews conducted with several sources as well as secondary data sources obtained from documents and books related to this research with data collection techniques obtained from interviews, observations, and studies. document. Data analysis techniques used in the form of data reduction, data presentation, and drawing conclusions. In this study it was found that the patrol carried out by the Demak Police Samapta Unit had been carried out in accordance with the expected conditions through three stages, namely the preparation stage, the implementation stage, and the termination stage. The influencing factors are divided into internal factors and external factors with internal factors consisting of supporting and inhibiting and external factors consisting of supporting and inhibiting. Thus, several solutions were found that could be taken by conducting training for patrol officers, re-determining patrol routes, equipping patrol officers with adequate equipment and weapons, equipping patrol vehicles with GPS, and establishing good relations with community leaders.